Penyuluhan dan Pelatihan Budidaya Jahe Merah di Kelompok Wanita Tani Desa Tanggeran, Kecamatan Sruweng, Kabupaten Kebumen - Barokah, Umi; Fatmawati, Nurlaila; Rahmawati, Aulia; Nugroho, Rahmat Joko (Kadiri University, 2022)
Community service activities were carried out in Tanggeran Village, Sruweng District, Kebumen Regency. This activity was carried out to increase public knowledge of the cultivation of red ginger plants and maximize village business funds in Kebumen Regency. The choice of red ginger is because this medicinal and herbal plant has a high economic value compared to other types of ginger. The methods used in this activity were counseling, discussion, and training to transfer knowledge of red ginger cultivation to participants. The participants who participated in this counseling and training were the